Treating genitourinary and pharyngeal gonorrhoea with single dose ceftriaxone. - Christophersen, J (1989)
The efficacy of ceftriaxone 250 mg given as a single intramuscular dose to treat genitourinary and pharyngeal gonorrhoea is compared with the outcome of the Danish standard treatment for uncomplicated genitourinary gonorrhoea, pivampicillin 1.4 g and probenecid 1 g, both given by mouth. The study comprised 327 patients for whom the diagnosis of gonorrhoea was made by microscopy of a methylene blue stained smear at their first visit to the clinic and for whom the diagnosis was later confirmed by culture of Neisseria gonorrhoeae. One hundred and seventy patients with genitourinary gonorrhoea (18 with and 152 without concomitant pharyngeal infection) were treated with ceftriaxone. One hundred and fifty seven (17 with and 140 without concomitant pharyngeal infection) were treated with pivampicillin. One week after treatment N gonorrhoeae was isolated from none of 18, 1/152, (1%), 11/17 (65%), and 6/140 (4%) patients, respectively. At a second attendance two weeks after treatment no further treatment failure was found. During the study period, a further 52 patients with pharyngeal infection (with or without concomitant genitourinary infection) that was shown by culture only were treated with a single intramuscular injection of 250 mg ceftriaxone. No treatment failure was observed in this group. Only minor adverse drug reactions were seen. Ceftriaxone 250 mg as a single intramuscular injection is therefore safe and effective in treating gonorrhoea, including pharyngeal infection.